Imposex, female sterility and organotin contamination of the prosobranch Nassarius reticulatus from the Portuguese coast - Barroso, C. M.; Moreira, M. H.; Bebianno, Maria (Marine Ecology Progress Series, 2002)
Samples of Nassarius reticulatus (L.) were obtained from May to July 2000 on the W Portuguese coast. N, reticulatus imposex (superimposition of male characters onto female prosobranchs) increased with the proximity of harbours. The percentage of imposex-affected females (%I) varied between 0 and 100%. The penis length index (PLI) and the relative penis length index (RPLI) were between 0 and 10.7 mm. and 0.0 and 92.1%, respectively. The vas deferens sequence index (VDSI) ranged from 0 to 5. The average oviduct stage (AOS) varied between 0.0 and 1.3. Sterile females (22 specimens) were found at 8 of the 40 sampling stations with frequencies between 5 and 50% of the total females sampled at each site. Sterility occurred only in females highly affected with imposex. Tributyltin (TBT) and triphenyltin (TPT) female body burden varied from <20 to 1368 and from <10 to 256 ng Sn g(-1) dry weight (dry wt), respectively. The TPT residue was, on average, 18 % of the TBT residue, and there was a highly significant correlation between TBT and lnTPT (r = 0.88, p < 0.001), Dibutyltin (DBT) and monobutyltin (MBT) female body burden varied from <34 to 721 and from < 24 to 703 ng Sn g(-1) dry wt, respectively, TBT represented the major fraction (34 to 60 %) of the total butyltins, followed by DBT (24 to 40 %) and MBT (10 to 31 %). Highly significant correlations (p <0.001) were established between the lnTBT female residue and the indices RPLI (r = 0.88), VDSI,5) (r = 0.81) and AOS (r = 0.72), as well as between TBT and percentage female sterility (%STER) (r = 0.61).